Towards a Cleaner Bay: Combating Marine Pollution to Revive Coastal Biodiversity in the Bay of Bengal - Hasana, Sk Mahmud (BIMRAD Journal, 2026)
Bay of Bengal is considered as one of the ecologically rich but environmentally sensitive maritime zones globally. The biodiversity along the coast comprising of mangroves, sea-grass bed, coral reefs, and many marine fishes & animals is instrumental in maintenance of fisheries and shore line protection as well as the livelihood of millions of people in Bangladesh. But increasing water pollution, caused by industrial wastes, plastic junks, farm waste and oil spillage among others have highly affected the quality of water and have impaired delicate environments. This paper will discuss the degree, origins and environmental implications of marine pollution in the Bay of Bengal, especially in terms of its effects on coastal biodiversity. The application of the mixed-method (which involves the analysis of empirical data samples, interviewing the stakeholders, and field observations) will reveal major pollution hotspots and evaluate the current mitigation framework. The results also indicate major enforcement gaps, waste management infrastructure gaps as well as gaps in cooperation between regions. The paper suggests a coordinated strategic approach that brings together the assimilation of tighter controls and regulation, community-based conservation, technological advancement, and furthering cooperation between regions to replenish and maintain the biodiversity of coastal areas. BIMRAD Journal VOLUME 6, ISSUE 1, DEC 2025; PP-64-82